F11-Receptor (F11R/JAM) Mediates Platelet Adhesion to Endothelial Cells: Role in Inflammatory Thrombosis - Babinska, Anna; Kedees, Mamdouh H.; Athar, Humra; Ahmed, Tahir; Batuman, Olcay; Ehrlich, Yigal H.; Hussain, M. Mahmood; Kornecki, Elizabeth (Thrombosis and Haemostasis, 2002)
The F11 receptor (F11R) is a cell adhesion molecule (CAM), member of the immunoglobulin superfamily found on the surface of human platelets, and determined to play a role in platelet aggregation, secretion, adhesion and spreading. The same molecule is present also at tight junctions of endothelial cells (EC) where it is known as JAM and acts as a CAM through homophilic interactions. The role of F11R/JAM in the interaction of platelets with endothelial cells was investigated in the current studies. We report here that washed human platelets adhere specifically to a matrix made of immobilized, recombinant sF11R. Furthermore, platelets adhere to cytokine(TNF-α, INF-γ) stimulated human umbilical vein endothelial cells (HUVEC), and approximately 40-60% of the adhesive force is exerted by homophilic interactions between the F11R of platelets and EC. This is evidenced by the inhibition of platelet adhesion to endothelial cells by recombinant soluble form of the F11R, and by two F11R peptides with amino acid sequences of the N-terminal region, and in the 1st Ig fold of the F11R, respectively. This study suggests a role for F11R in the adhesion of platelets to cytokine-inflamed endothelial cells and thus in thrombosis and atherosclerosis induced in non-denuded blood vessels by inflammatory processes. Agents that block the F11R-mediated adhesion of platelets to EC may be of therapeutic value in controlling thrombosis and preventing heart attacks and stroke.
Keywords: Human platelet F11 receptor (F11R); junctional adhesion molecule (JAM); platelet aggregation; adhesion; F11R peptides; HUVEC